Web usability and the mediating effect of persuasion towards online purchase - Robert Jeyakumar Plamel Nathan (2015)
The propulsion of the business world into the new era of Information Communication Technology (ICT) has placed Internet marketing websites in the limelight, playing an important role in reaching specific focus groups comprising users who vary in many aspects. Having looked at some aspects pertaining to the usability of Internet marketing websites, and the challenges associated with good website designs incorporating usability factors, there is evidently a research gap in the understanding of the perceptions of Students Internet Users (SIUs) on Web usability and how this affects their online buying behaviour. General Internet-based studies have proposed web usability guidelines for all Internet users without focusing on a particular market segment, contrary to the science of marketing that advocates businesses to target, segment and position their products for their intended customers. Hence, this research is set forth to investigate the role of usability, design, credibility and persuasion to the purchase intention of SIUs towards Internet marketing websites from the perspective of SIUs from 24 industries of interest. Empirical results via Partial Least Square Structured Equation Modelling (PLS-SEM) revealed that all research variables were found to significantly contribute towards SIU’s purchase intention towards websites from 24 industry categories. Industry is found to be a moderator, while ‘Persuasion’ is proven to have a strong mediation effect in the research framework. This research bridged existing gaps in empirical Internet marketing research devoid of a specific target market segment. The finding also addresses the gap in theory by including persuasion to the equation. In TAM Model, persuasion mediates the relationship between the “perceived ease of use” and “behavioural intention to use”. As for ELM, the finding helps to extents the ELM model by linking “Persuasion Outcome” to purchase intention. Further, some research and practical implications are provided on specific guidelines for cyberpreneurs and technopreneurs in the design and presentation of usable and highly marketable websites to reach the market segment comprising SIUs who make up a formidable bulk of the millennials affected by online purchasing. Research limitations and direction for future research are also discussed.